ANALISA KEKERASAN DAN FRACTURE TOUGHNESS ALUMINA DIPERKUAT SERBUK ALUMINIUM DAN TEMBAGA - Hendriwan Fahmi (Jurnal Teknik Mesin (JTM), 2015)
Composite is a big picture in the development of today's materials science engineering. This material seems to be able to replace the role of metallic and non-metallic materials. The purpose of this study was to determine the effect of the addition of aluminum powder (Al) and copper (Cu) in the matrix Alumina (Al2O3) on the hardness and fracture toughness values. Aluminum powder is made with water atomization process and copper powder prepared by centrifugal atomization process. Aluminum powder and copper followed by a sifting process using mesh size 50-100 to get a powder size of 125-150 µm. From the steps followed by the process of mixing the composition variation of 100% volume of Al2O3, 90% Al2O3 + 10% Volume weight of Al and Cu, 80% Volume Al2O3 + 20 wt% Al and Cu, 70% Volume Al2O3 + 30 wt% Al and Cu, 60% Volume Al2O3 + 40 wt% Al and Cu. Then do the process of compacting pressure with of 140 MPa. Sintering process is done using a furnace with a temperature of 1150 o C with Heating rate 5° C / min. In this study, the highest value is 84 HRc hardnessand average of 76.83 HRc. and fracture toughness (K1C) highest this 1,388 obtained at 60% volume composition Al2O3 + 40 wt% Al and Cu with an average bending stress of 1,227 MPa.m1 / 2 .